Geopolitical confrontation between Russia and the Ottoman Empire in the North Caucasus in the first half of the XIX century: the main causes and historical consequences - R. I. Pliev (Гуманитарные и юридические исследования, 2024)
Introduction. The article analyzes geopolitical confrontation between Russia and the Ottoman Empire in the North Caucasus in the first half of the 19th century. The author identifies the main prerequisites that became the reason for the historical confrontation, formulates the strategic interests of the parties to the conflict, characterizes the economic, political and cultural motives that increased geopolitical competition in the North Caucasus during the period under review. Materials and Methods. The study is based on the analysis of texts by domestic and foreign scholars studying the Caucasus, collections of published documents and materials obtained from the funds of the central archives of the Russian Federation (AVP RI, RGADA). Retrospective, historical-genetic, historical-comparative and personalbiographical methods were used as methods of historical and political research.The analysis of the underlying preconditions for the actualization of the Ottoman factor in the escalation of the events of the Caucasian War is carried out. The study specifies objective and subjective factors that contributed to the natural clash of interests of the two countries in the North Caucasus as the region in which the rational economic and geopolitical motives of the two empires were supplemented by ideological considerations aimed at protecting the peoples, belonging to Islamic and Orthodox civilizations. Analysis. Special attention is paid to deep historical roots of the Russian-Turkish conflict in the Caucasus in the 19th century formed by a shift in the balance of power between states during the 18th century. Successful conquests of the Russian army deprived the Ottoman Empire of geopolitical influence in the vast areas of the North Caucasus and the Northern Black Sea region. Also, a special place in the study is occupied by the problem of the role of Western countries in the escalation of the conflict between St. Petersburg and Istanbul during the historical period under review. Results. The author emphasizes the fact that the anti-Russian position of Great Britain and France on the Caucasian issue was of great importance in the context of the development of events of the Caucasian War. At the same time, the pro-Ottoman policy of London and Paris was dictated by realistic considerations of these countries, which sought, by encouraging Turkish revanchism, to restrain Russian expansion in territories of strategic interest to them. From this point of view, the Caucasian War is considered by the author as part of the “great game” of Russia and Great Britain, which competed for leadership on the Eurasian continent.